Scoping Review: Interprofessional Simulation as an Effective Modality to Teaching Interprofessional Collaborative Competencies in the Emergency Department - Barton, Lily; Lackie, Kelly; Miller, Stephen G. (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2023)
Background: A scoping review was conducted to map the current body of research pertaining to simulation-enhanced interprofessional education (Sim-IPE) as a modality for teaching interprofessional collaboration (IPC) in the emergencydepartment (ED).